Analisis Prinsip, Tantangan, dan Implikasi Pengembangan Kurikulum PAI untuk Pendidikan - Reza Noprial Lubis (TARBIYAH: Jurnal Pendidikan Islam, 2022)
The development of the Islamic Religious Education (PAI) curriculum is a crucial aspect of shaping students' character and morals in the modern era. This study aims to identify the fundamental principles underlying the development of the PAI curriculum, as well as the challenges faced during its implementation. A qualitative method using a literature review approach was employed, analyzing relevant literature on curriculum, education, and PAI practices. The findings indicate that principles such as relevance, integration, connection, and sustainability are essential foundations for designing an effective curriculum. Additionally, challenges such as educator resistance, lack of resources, and socio-cultural changes were identified as barriers to curriculum development. Recommendations for enhancing the effectiveness of the PAI curriculum include training for educators, collaboration with stakeholders, and regular evaluation of the curriculum. By understanding these principles and challenges, it is hoped that the development of the PAI curriculum can positively contribute to creating a generation of character and moral integrity, in line with Islamic values in a rapidly evolving global context.